Reciprocal Relationship between Subjective Well-Being, Social Media Engagement and Compulsive Buying Behavior - Derriawan, Derriawan; Hendryadi, Hendryadi; Suryani, Suryani; Noor, Laili Savitri; Okrivina, Amelia (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2024)
This study aimed to investigate the interplay between subjective well-being (SWB), social media engagement (SME), and compulsive buying behavior (CBB). It explored long-term and reciprocal connections among these factors using a longitudinal design with a 2-wave investigation of 226 employees from various sectors in Jakarta, Indonesia. Partial Least Squares Structural Equation Modeling (PLS-SEM) cross-lagged analysis found that SWB at Time 1/Time 2 negatively predicted SME and CBB at the same times, indicating long-term influences. Additionally, SME at Time 1 and CBB at Time 2 significantly predicted SWB at Time 2. The study also found a positive relationship between SME and CBB at both times. This research contributes to the literature by empirically examining the reciprocal relationship among SWB, SME, and CBB, focusing on the association between SWB and CBB.   Keyword : compulsive buying behavior; reciprocal relationship; social media engagement; subjective well-being; longitudinal